Strategi Public Relations Untuk Menciptakan Minat Pengunjung Ke Galeri Indonesia Kaya - Hessy Lestari; Lestari Nurhajati (LONTAR: Jurnal Ilmu Komunikasi, 2019)
One of the most important tools in gallery is Public Relations. The existence of Public Relations in aGallery can be a bridge between the gallery with its public. The purpose of Public Relations in aGallery is to disseminate information, create, and maintain good harmonious relationships in orderto get a positive image of the Gallery. However, the abundance of Galleries in Jakarta, causes alack of public interest in visiting Gallery Indonesia Kaya. This causes the need for a PublicRelations strategy that is used to increase visitors’. This research was conducted by usingqualitative method through interview and observation. From the results of interviews andobservation, researchers found that the Gallery Indonesia Kaya performs strategies of PublicRelations to increase visitor’s interest. Researchers also found that Gallery Indonesia Kaya has notsucceeded in doing strategy of Public Relations to increase visitors’ interest because theinconsistency between strategy and hope which executed with expectation to be achieved.